Mathematical creativity in student's solutions to open-ended problems - Lapitan, May Ann B. (2013)
The study describes and evaluates the mathematical creativity shown in the solutions of the participants to open-ended problems in mathematics. This study employed survey method research in gathering and analysing data. The solutions were described and evaluated using the three components of mathematical creativity, namely fluency, flexibility and originality. A Problem Solving Test composed of three validated open-ended problems in Algebra was administered to 45 third year high school students. A Scoring Rubric was developed and content was validated by experts in mathematics. The rubric was used to evaluate solutions according to the mathematical creativity. It was also found that among the components of mathematical creativity; the participants performed best in fluency (67.70%) and least in originality (2.80%), implying that generating many correct solutions is the easiest to attain while coming up with original solutions is the most difficult. This study may also serve as basis for teachers in constructing open-ended problems and scoring rubric to evaluate it and has a great implications of changing how mathematics is being taught and evaluated.
Keywords: Mathematics; Problem solving (Mathematics)